Assessing educational infrastructure delivery in the Seshego Circuit, Limpopo Province - Mavundla, Yvonne Thembalethu (University of Limpopo, 2016)
In post - apartheid South Africa, a lack of adequate financial and physical resources in historically disadvantaged public schools is a major barrier to effective teaching and learning. Schools in the rural South Africa are part of communities and therefore can be seen as microcosms of societal conditions. The national Ministry of Basic Education has a responsibility to provide a necessary educational infrastructure to all public schools. Other relevant stakeholders such as the community and businesses need to assist the government to supplement the delivery of educational infrastructure. It is against this background that the study undertakes to assess the delivery of educational infrastructure that will lead to service delivery improvement. Some of the considered focused areas in the study include the demographics of the schools, the condition of the school infrastructure and the legislative frameworks that serve to support educational infrastructure. Literature on various forms has been reviewed in order to understand the regulatory framework upon which the delivery of educational infrastructure is based. The study used the qualitative method to investigate the delivery of educational infrastructure. The main findings indicated that educational infrastructure in rural schools is generally poor and there is a shortage of physical resources in schools. It is clear in this regard that current processes are hampering the Department of Basic Education to improve service delivery in public schools especially those that are in rural areas. vi KEYWORDS  Department of Basic Education in Limpopo Province  Educational infrastructure  Assessment  Physical resources  Public schools  Service delivery  Teaching and learning
Thesis (MPA.) -- University of Limpopo, 2016
Keywords: Public schools; Service delivery; Teaching and learning; Educational infrastructure; Basic education; Constructivism (Education); Educational planning